2016 International Joint Conference on Neural Networks (IJCNN) 2016
DOI: 10.1109/ijcnn.2016.7727411
|View full text |Cite
|
Sign up to set email alerts
|

Human skeleton matching for e-learning of dance using a probabilistic neural network

Abstract: Abstract-With the growing interest in the domain of human computer interaction (HCI) these days, budding research professionals are coming up with novel ideas of developing more versatile and flexible modes of communication between a man and a machine. Using the attributes of internet, the scientists have been able to create a web based social platform for learning any desired art by the subject himself/herself, and this particular procedure is termed as electronic learning or e-learning. In this paper, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was shown that a cross-validation type PNN produced better results (by a few percent), although the complexity order increases from O(n) to O(n 2 ). Dance routines were identified with 91.7% accuracy using captured Kinect video images by extracting features following the estimation of angles and displacement distances of limbs during movement [31,32]. It is beneficial to reduce the complexity by using an efficient representation of the data using as short a code word as possible.…”
Section: Pnn-based Techniquesmentioning
confidence: 99%
“…It was shown that a cross-validation type PNN produced better results (by a few percent), although the complexity order increases from O(n) to O(n 2 ). Dance routines were identified with 91.7% accuracy using captured Kinect video images by extracting features following the estimation of angles and displacement distances of limbs during movement [31,32]. It is beneficial to reduce the complexity by using an efficient representation of the data using as short a code word as possible.…”
Section: Pnn-based Techniquesmentioning
confidence: 99%
“…In this paper, we focus on a markerless capture method based on the skeletal joint data of human motion utilizing a Kinect camera in a motion-capture studio environment for the classification of K-pop dance movements. The previous works have been focused on ballet analysis [ 16 , 17 ], video recommendation based on dance styles [ 18 ], dance pose estimation [ 19 , 20 ], dance animation [ 21 ], and e-learning of dance [ 22 ]. While some ballet movements and dance pose estimation have previously been studied in various aspects [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], nobody has yet performed research on K-pop dance movements using Kinect sensors to address the problem of dance plagiarism.…”
Section: Introductionmentioning
confidence: 99%